Data Governance Improvement Strategy for Peer-to-Peer Lending Sharia in Indonesia: Study Case PT ABC - Priastomo, Ristyo Yogi; Ruldeviyani, Yova; Gunawan, Adi; Al Haq, Muhammad Hezby; Utami, Aisyah Nurlita (AI Society & STMIK Indonesia, 2024)
Abstract—Financial Technology (fintech) is a company that supervised by the Indonesian Financial Services Authority (OJK) and fintech associations which has strict regulations. Well-defined data management can support organizations to comply with mandatory regulations. This research was conducted on a sharia peer-to-peer lending fintech in Indonesia with the aim of solving data governance problems in organizations by measure of Data Governance Maturity Level to get recommendations strategies to improve the implementation of data governance in the organization. The measurement was carried out using IBM Data Governance Maturity Model Framework. After validation and finalization of the assessment, the results showed that the average score was 2.47. It's shown that currently at the Managed level. Some domains need to be improved in the future, data value creation, data organizational structure and awareness, data policies and rules and data stewardship.